Workload and job satisfaction among nurses in a tertiary level hospital (Asian Journal of Medical and Biological Research, 2020)
Workload and job satisfaction are interrelated and have an impact on health care. A cross sectional study was conducted to assess the workload and job satisfaction among nurses in a tertiary level hospital, Rajshahi. Three hundred and eighty four Nurses were selected and interviewed with semi-structured questionnaire. Collected data were checked and transferred in to SPSS version 25 for analysis. Frequency, Percentage, Mean, SD and other statistics were calculated. In the study, 63.8 % of the respondents ages were within 21-30 years and majority (94.2%) was female. More than half 57.03% of the respondents had expressed low job satisfaction, 40.62% expressed moderate satisfaction and only 2.34% of nurses were highly satisfied with their job. About 25% respondent’s opinion regarding workload in surgical wards and 18% in medicine ward. In this study, nurse patient’s ratio in- pediatric medical unit was- 16:1, surgical unit- 15:1, medicine unit-14:1. About 96.9% got support from colleague, 88.5% respondents realize shortage of staff in that hospital. In this study near half of the nurses had not enough time to provide emotional support to the patient and almost 90% stated on shortage of staff nurses in the hospital. Fifty percent of the nurses expressed on excess workload and more than half of the nurses satisfied regarding nursing care given to the patients. Among the nurses 30% dissatisfied with the hospital work environment and overall job security. In this study, 88.5% respondent’s opined regarding shortage of staff nurses in that hospital. Health facilities requires increase of nursing personnel.Asian J. Med. Biol. Res. June 2020, 6(2): 359-365